2015
DOI: 10.1186/s13148-015-0096-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic alterations of netrin-1 receptors in gastric cancer with chromosomal instability

Abstract: BackgroundThe gene expressions of netrin-1 dependence receptors, DCC and UNC5C, are frequently downregulated in many cancers. We hypothesized that downregulation of DCC and UNC5C has an important growth regulatory function in gastric tumorigenesis.ResultsIn the present study, a series of genetic and epigenetic analyses for DCC and UNC5C were performed in a Japanese cohort of 98 sporadic gastric cancers and corresponding normal gastric mucosa specimens. Loss of heterozygosity (LOH) analyses and microsatellite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…Currently, DCC is known to be involved in the following biological processes: guidance of developing axons,4 induction of apoptosis [18], control of colorectal tumorigenesis [19], and angiogenesis [20]. DCC alterations are apparent in early-stage gastric cancers, emphasizing the importance of this growth regulatory pathway in gastric carcinogenesis [21]. Significant differences were observed between cases without metastasis or local recurrences versus those with metastasis or local recurrences, suggesting that a decrease in DCC expression might influence the prognosis of patients with breast cancer [22].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, DCC is known to be involved in the following biological processes: guidance of developing axons,4 induction of apoptosis [18], control of colorectal tumorigenesis [19], and angiogenesis [20]. DCC alterations are apparent in early-stage gastric cancers, emphasizing the importance of this growth regulatory pathway in gastric carcinogenesis [21]. Significant differences were observed between cases without metastasis or local recurrences versus those with metastasis or local recurrences, suggesting that a decrease in DCC expression might influence the prognosis of patients with breast cancer [22].…”
Section: Discussionmentioning
confidence: 99%
“…5,12,37,38 Two other studies also showed loss of expression of these receptors by methylation in gastric cancer. 39,40 However, the expression levels of Netrin-1 were not measured and compared with the expression levels of the receptors. Therefore, further preclinical and clinical studies are needed to address the significance of Netrin-1 as a biomarker in cancer.…”
Section: Netrin-1 and Cancer: A Potential Biomarker?mentioning
confidence: 99%
“…Gastric cancer is the second-most common cause of death among all cancer types for both sexes with an annual mortality of 952 000 individuals worldwide . Gastric cancer is more common in Asia than in the rest of the world and is especially common in China and Japan . The type of gastric cancer with the highest incidence is adenocarcinoma .…”
Section: Introductionmentioning
confidence: 99%
“…1 Gastric cancer is more common in Asia than in the rest of the world and is especially common in China and Japan. 2 The type of gastric cancer with the highest incidence is adenocarcinoma. 3 Previous studies have indicated that current therapies for gastric cancer involve combining several strategies, including surgery, chemotherapy, and radiation.…”
Section: ■ Introductionmentioning
confidence: 99%